Vasoactive intestinal peptide increases intracellular calcium in astroglia: synergism with alpha-adrenergic receptors. - Fatatis, A (1994)
In type I astrocytes from rat cerebral cortex, vasoactive intestinal peptide (VIP) at concentrations below 1 nM evoked an increase in intracellular calcium ion concentration. This response, however, was observed in only 18% of the astrocytes examined. alpha-Adrenergic stimulation with phenylephrine or norepinephrine also resulted in an intracellular calcium response in these cells and the threshold sensitivity of astrocytes to phenylephrine was vastly different from cell to cell. Treatment of these astrocytes with VIP (0.1 nM) together with phenylephrine at subthreshold concentrations produced large increases in intracellular Ca2+ concentration ([Ca2+]i) and oscillations. The continued occupation of the alpha-adrenergic receptor was required for sustained synergism. Both alpha-receptor stimulation and stimulation with the mixture of agonists induced the cellular calcium response by triggering release of calcium from cellular stores, since the response persisted in the absence of extracellular calcium. Furthermore, thapsigargin pretreatment, which depletes intracellular stores, abolished the agonist-induced [Ca2+]i response. VIP (0.1 nM) and phenylephrine were found to increase cellular levels of inositol phosphates; however, there was no apparent additivity in this response when the agonists were added together. These observations suggest a calcium-mediated second messenger system for the high-affinity VIP receptor in astrocytes and that alpha-adrenergic receptors act synergistically with the VIP receptor to augment an intracellular calcium signal. The synergism between diverse receptor types may constitute an important mode of cellular signaling in astroglia.